2017
DOI: 10.1002/art.40114
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil Versus Placebo for Systemic Sclerosis–Related Interstitial Lung Disease: An Analysis of Scleroderma Lung Studies I and II

Abstract: Objective To compare mycophenolate (MMF) with placebo for the treatment of systemic sclerosis-related interstitial lung disease (SSc-ILD). Methods Participants enrolled in the placebo arm of Scleroderma Lung Study (SLS) I and the MMF arm of SLS II were included. SLS I randomized participants to oral cyclophosphamide (CYC) versus placebo for 1 year, while SLS II randomized participants to MMF for 2 years versus oral CYC for 1 year followed by 1 year of placebo. Eligibility criteria for SLS I and II were nearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
84
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 25 publications
5
84
0
2
Order By: Relevance
“…The use of GCs among experts was not high in our study; however, they have been used more frequently in some trials . Experts incorporated MMF (as first‐line treatment) and IV CYC (as third‐line treatment) to treat SSc patients with high MRSS scores.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The use of GCs among experts was not high in our study; however, they have been used more frequently in some trials . Experts incorporated MMF (as first‐line treatment) and IV CYC (as third‐line treatment) to treat SSc patients with high MRSS scores.…”
Section: Discussionmentioning
confidence: 85%
“…Management of ILD induction therapy has changed considerably. After the Scleroderma Lung Studies (SLS 1 and SLS 2) , experts have changed their first‐line preference from CYC to MMF. Oral CYC was used in the SLS studies, but the majority of experts said that if they used CYC, it would be mostly IV.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Conventional therapy has limited benefit on disease control and modest impact on mortality. [3][4][5][6] Three randomized studies have shown that autologous hematopoietic stem cell transplantation (AHSCT) has superior efficacy when compared with conventional therapy for SSc. [7][8][9][10] Nevertheless, clinical guidelines and immune monitoring studies after AHSCT aim to further improve patient care and transplant outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…After 12 months, the benefits of this treatment were no different from placebo, although FVC showed a trend towards improvement in the treatment group compared with the placebo group that did not reach statistical significance [120]. In the Scleroderma Lung Study II (SLS II), mycophenolate mofetil (MMF) was as efficacious as oral cyclophosphamide in improving cough-specific measurements [121], which was also observed when the data from both SLS studies were combined, to include the placebo control from SLS I [122] However, the tolerability of MMF was superior to cyclophosphamide and MMF is now used as a first line treatment in most centers [123]. The optimal dose of MMF for the treatment of SSc-associated ILD is probably 3g/day, which was the target dose in the SLS II trial, although for patients who struggle to tolerate 3/g day, 2g/day might be considered.…”
Section: [H2] Treatment Approaches For Lung Fibrosismentioning
confidence: 95%